2014
DOI: 10.1111/1751-7915.12236
|View full text |Cite
|
Sign up to set email alerts
|

A chromosomally encoded T7 RNA polymerase‐dependent gene expression system for Corynebacterium glutamicum: construction and comparative evaluation at the single‐cell level

Abstract: Corynebacterium glutamicum has become a favourite model organism in white biotechnology. Nevertheless, only few systems for the regulatable (over)expression of homologous and heterologous genes are currently available, all of which are based on the endogenous RNA polymerase. In this study, we developed an isopropyl-β-d-1-thiogalactopyranosid (IPTG)-inducible T7 expression system in the prophage-free strain C. glutamicum MB001. For this purpose, part of the DE3 region of Escherichia coli BL21(DE3) including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 73 publications
4
59
0
Order By: Relevance
“…S2 in the supplemental material) using nonexposed cIPTG were found to be moderate in BHI medium (up to 1.5-fold increase in comparison to control strains) and CGXII medium (up to 2.2-fold). As reported in the literature (50), basal expression levels of the system used here were found to be elevated in CGXII minimal medium and increased with ongoing cultivation times. The dynamic range of induction, however, was high and comparable in BHI medium (63-fold for cIPTG and 61-fold for IPTG).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…S2 in the supplemental material) using nonexposed cIPTG were found to be moderate in BHI medium (up to 1.5-fold increase in comparison to control strains) and CGXII medium (up to 2.2-fold). As reported in the literature (50), basal expression levels of the system used here were found to be elevated in CGXII minimal medium and increased with ongoing cultivation times. The dynamic range of induction, however, was high and comparable in BHI medium (63-fold for cIPTG and 61-fold for IPTG).…”
Section: Resultssupporting
confidence: 83%
“…In BHI medium, a second population with lower fluorescence intensity occurred after 20 h of overexpression, whereas prolonged expression in CGXII medium obviously resulted in the formation of a second population with increased YFP accumulation. In principle, expression heterogeneity has recently been described for a similar expression setup in C. glutamicum (50). Notably, flow cytometric single-cell analysis using propidium iodide-based LIVE/DEAD staining (43) further suggested that light induction did not affect membrane integrity and thus cell viability (see Fig.…”
Section: Resultsmentioning
confidence: 89%
“…PCR fragments covering the respective genes were generated using the oligonucleotides listed in Supporting Information Table S3 and included overlaps between the PCR fragments and the pEKEx2 backbone. Plasmid pMKEx1 was constructed by integration of the expression cassette of pET-TEV (Bussmann et al, 2010) into plasmid pJC1, as described before for pMKEx2 (Kortmann et al, 2015). The resulting products were used to transform E. coli and the plasmids were isolated and checked for correctness by sequencing.…”
Section: Construction Of Plasmids and Deletion Mutantsmentioning
confidence: 99%
“…Also, extensive bioprocess knowledge with C.   glutamicum and methods for genetic manipulation are available because this microbe is a major producer for amino acids at industrial scale for decades [8]. Recently, the construction of a C.   glutamicum strain harboring the DE3/T7 expression system was reported, allowing to control gene expression levels for intracellular protein production [9]. This system is based on the prophage-cured C.   glutamicum strain MB001, which was shown earlier to be beneficial for intracellular protein production [10].…”
Section: Introductionmentioning
confidence: 99%